2013
DOI: 10.1088/0067-0049/206/1/1
|View full text |Cite
|
Sign up to set email alerts
|

MID-INFRARED PROPERTIES OF NEARBY LUMINOUS INFRARED GALAXIES. I. SPITZER INFRARED SPECTROGRAPH SPECTRA FOR THE GOALS SAMPLE

Abstract: The Great Observatories All-Sky LIRG Survey (GOALS) is a comprehensive, multiwavelength study of luminous infrared galaxies (LIRGs) in the local universe. Here we present low resolution Spitzer Infrared Spectrograph spectra covering 5-38 μm and provide a basic analysis of the mid-IR spectral properties observed for nearby LIRGs. In a companion paper, we discuss detailed fits to the spectra and compare the LIRGs to other classes of galaxies. The GOALS sample of 244 nuclei in 180 luminous (10 11 L IR /L < 10 12 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
395
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 192 publications
(419 citation statements)
references
References 36 publications
21
395
3
Order By: Relevance
“…This has been done by exploiting 5-8 μm spectroscopy (e.g., Nardini et al 2010) and the characteristics of several features in the L (3-4 μm) and M (4-5 μm) bands (Imanishi & Dudley 2000;Risaliti et al 2006;Sani et al 2008;Risaliti et al 2010): the 3.3 μm polycyclic aromatic hydrocarbon (PAH) emission feature, the bare carbonaceous 3.4 μm absorption feature, and the slope of the continuum. The 6.2 μm (e.g., Stierwalt et al 2013Stierwalt et al , 2014 and 7.7 μm PAH features (e.g., Veilleux et al 2009), the presence of highexcitation MIR lines (e.g., [Ne V] 14.32 μm, Veilleux et al 2009), or the radio properties (e.g., Parra et al 2010;Romero-Cañizales et al 2012a;Vardoulaki et al 2015) have also been used to infer the presence of a buried AGN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been done by exploiting 5-8 μm spectroscopy (e.g., Nardini et al 2010) and the characteristics of several features in the L (3-4 μm) and M (4-5 μm) bands (Imanishi & Dudley 2000;Risaliti et al 2006;Sani et al 2008;Risaliti et al 2010): the 3.3 μm polycyclic aromatic hydrocarbon (PAH) emission feature, the bare carbonaceous 3.4 μm absorption feature, and the slope of the continuum. The 6.2 μm (e.g., Stierwalt et al 2013Stierwalt et al , 2014 and 7.7 μm PAH features (e.g., Veilleux et al 2009), the presence of highexcitation MIR lines (e.g., [Ne V] 14.32 μm, Veilleux et al 2009), or the radio properties (e.g., Parra et al 2010;Romero-Cañizales et al 2012a;Vardoulaki et al 2015) have also been used to infer the presence of a buried AGN.…”
Section: Introductionmentioning
confidence: 99%
“…The source has a star formation rate (SFR) of 41.3 M e yr −1 (Howell et al 2010), is in an early merging stage (i.e., stage B or 2, following the classification of Stierwalt et al 2013), and is interacting with the galaxy NGC 6285 (NGC 6286N) located at a distance of ∼1.5 arcmin (∼33 kpc, projected distance; see Figure 1 and panel four of Figure 2). …”
Section: Introductionmentioning
confidence: 99%
“…Although these systems are relatively rare in the local universe, Le Floc'h et al (2005) have shown that high infrared luminosities may have been the norm at redshifts beyond 0.7. To understand these cosmically important objects and the physical processes that occur in them, the Great Observatory All-Sky LIRG Survey (GOALS; Armus et al 2009) team has compiled data across a number of different wavelength regimes, including Hubble Space Telescope imaging in the optical (Kim et al 2013) and near-infrared (Haan et al 2011), Chandra X-ray observations, (Iwasawa et al 2011), Spitzer spectra in the mid-infrared (Stierwalt et al 2013), GALEX observations in the near and far ultraviolet (Howell et al 2010), and Herschel Space Telescope spectra in the far-infrared (Díaz-Santos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the mid-IR spectra of the central components are very diverse, implying that observed variations of the integrated properties of local (U)LIRGs reflect processes that are occuring predominantly in their nuclei. The low-resolution IRS spectra spanning 5-58 μm for 244 nuclei in 180 (U)LIRGs in the GOALS sample are presented by Stierwalt et al (2013), along with the following results: Both silicate depth and mid-IR continuum slope rise with increasing L ir ; on average late-stage mergers have steeper mid-IR slopes and higher dust obscuration than early and intermediate stage mergers; when AGN contributions to local LIRGs and high-z sub-mm galaxies (SMGs) are removed, there is a strong resemblance between the average local LIRG and SMGs dominated by star formation.…”
Section: Survey Resultsmentioning
confidence: 99%